I want two birthdays! - Ross, Tony (Andersen Press USA : Distributed in the U.S. and Canada by Lerner Pub. Group, 2010)
A little princess decides that two birthdays would be better than one, and three better than two, until every day becomes her birthday, but she soon realizes that the more birthdays she has, the less special they are.